2015
DOI: 10.1007/s10864-015-9219-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Efficacy of the PEAK Relational Training System Using a Randomized Controlled Trial of Children with Autism

Abstract: The present investigation sought to examine the efficacy of the instructional curriculum described in the Direct Training Module of the PEAK Relational Training System on the language repertoires, as measured by the PEAK direct assessment, of children diagnosed with autism or related developmental disabilities. Twenty-seven children diagnosed with pervasive developmental disorders were evaluated using the PEAK direct training assessment protocol prior to assignment to control and experimental groups. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 8 publications
1
23
0
2
Order By: Relevance
“…The PEAK group demonstrated greater increases both in PDA total scores and change scores relative to a quasi‐experimental control group. The results further extend upon the study conducted by McKeel et al () and the study conducted by Belisle et al () by demonstrating that significant skill acquisition can occur when procedures are conducted by frontline staff rather than trained graduate students. This finding supports the generalizability of the PEAK‐DT curriculum in human service settings where practitioners with specialized training in ABA may be scarce.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PEAK group demonstrated greater increases both in PDA total scores and change scores relative to a quasi‐experimental control group. The results further extend upon the study conducted by McKeel et al () and the study conducted by Belisle et al () by demonstrating that significant skill acquisition can occur when procedures are conducted by frontline staff rather than trained graduate students. This finding supports the generalizability of the PEAK‐DT curriculum in human service settings where practitioners with specialized training in ABA may be scarce.…”
Section: Discussionmentioning
confidence: 99%
“…This limitation certainly reduces the internal validity of this study but also provides greater external validity by allowing for the idiosyncratic nature of the classroom environment to influence the data. Despite looser controls imposed upon the implementers relative to the study conducted by McKeel et al (), the participants in the PEAK group demonstrated significantly greater skill acquisition on the PDA relative to the control group. A fourth limitation was that the PDA was used as the assessment of skill acquisition, and so further research is needed to evaluate the effect of PEAK instruction on the acquisition of other untrained skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the first intervention‐outcome evaluation of the PEAK‐DTM, McKeel, Dixon, Daar, Rowsey, and Szekely () included 27 students with autism and other developmental disabilities in a 1‐month, randomized experimental‐control group design. The control group participants ( n = 13) received treatment as usual through special education services at their schools.…”
Section: Derived Relational Responding and Verbal Behaviormentioning
confidence: 99%
“…Results showed that the higher the PEAK assessment score, the higher the IQ of individuals with intellectual disabilities. Research and data has also suggested that PEAK may be especially useful as an assessment and curriculum guide for individuals with autism (Dixon, Belisle, Whiting, & Rowsey, 2014;McKeel, Dixon, Daar, Rowsey, & Szekely, 2015;Rowsey, Belisle, & Dixon, 2015). Current studies are beginning to address the validity of PEAK-E.…”
mentioning
confidence: 99%